Application of integration model for recovery fund in takaful education plan - Puspa Liza, Ghazali; Lazim, Omar; Mustafa, Mamat (Pushpa Publishing House, 2016)
The main purpose of the Takaful education plan is to provide fund for tertiary education. Currently, the Takaful education plan is offered to all children without taking much into consideration of their condition, whether they are the learning disabled children (ADHD, autism and dyslexia) or not, and there is no Takaful education plan that provides plan for the learning disabled children (LDC) specifically. LDC are different in terms of their diet and learning way due to their disability and these incur a high cost for parents in preparing suitable needs for their special children. The premium life tables for the new Takaful education plan which are based on the Wakalah model are set up using the integration model. From this model, a fund for the learning disabled children’s recovery (dietary supplement, learning and parenting skills) is set up for 3 years, together with the education fund, which will mature when the child reaches the age of 21. This new education plan is able to help the parents to minimize their cost, together with the additional benefits that they will get as they participate in this plan.